Aplicación de la contabilidad en “EVERLAST HOTEL” de la ciudad de Zamora, periodo del 1 de octubre al 31 de diciembre del 2017 - Amay Armijos, Jhuliana Elizabeth (2018)
The thesis work called: APPLICATION OF ACCOUNTING IN "EVERLAST HOTEL" OF THE CITY OF ZAMORA, PERIOD FROM OCTOBER 1 TO DECEMBER 31, 2017, was developed in order to keep an efficient control and organization of the activities carried out as it is the provision of both lodging and food services, through accounting tools that allow the determination of reliable and timely financial and financial information for the successful decision making of the hotel owners. The application of the accounting allowed to fulfill with the objectives proposed in the present thesis work; concordant, from the first objective where a chart of accounts according to the needs and services provided by the hotel was prepared, the same one that is duly ordered and codified with its respective manual of description of the accounts that facilitates the correct registration of the transactions. Within the second objective was the initial inventory survey by physical verification of assets, rights and obligations, to know the assets, liabilities and assets held by the hotel on October 1, 2017, and with the values obtained was elaborated the Initial Situation Status. Complying with the third objective, auxiliary daily purchase records were designed, daily auxiliary records of the service provided, auxiliary records of accounts receivable, comandas detailing the additional service provided during the guests' stay, payment roles and provision roles; all these assistants allowed to record and detail the accounting information collected from daily operations or transactions extracted, from the support documentation in invoices, withholdings, account statements, etc. 5 For the last objective the accounting process was developed, starting with the documents or vouchers for its registration in the Daily Book, General Ledger, Verification Balance, Worksheet; the corresponding adjustments related to depreciation and consumption were made, the closing of income and expense books; concluding with the elaboration of the Financial Statements, the same ones that allowed to reflect the economic and financial situation of the hotel in the period from October to December of the year 2017. At the end of the present work it was possible to highlight the positive aspects of accounting in this type of service companies, which, although small, still need accounting tools that allow their owners to carry out their activities not empirically if not correctly through a adequate accounting control and obtain financial information that allows them to take fruitful measures for their economic development and improvement in the hotel area. The application of the accounting in the Everlast hotel allowed to determine the patrimony with which it has $ 319,703.28; and an unsatisfactory result from the October to December fiscal year obtaining a loss of $ 226.53; Thus, in order to improve their profitability, it is convenient for owners to adopt new and innovative strategies in the quality of service provision, such as in the improvement of their facilities, which allows them to obtain more profitable income in each of the periods and for So much a growth of the hotel to future.